System-level object-orientation in the specification and validation of embedded systems - Fernandes, João M. (2001)
The main aim of this paper is to present how the Unified Modeling Language (UML) can be used as the notation to specify the requirements of an embedded system. By using a relatively small, but real, system (a supervision application) as a running example, the paper illustrates the design flow that can be followed during the analysis phase of complex control applications. To assure the continuous mapping of the models, the authors propose some guidelines to transform the use case diagrams into a single object diagram, which is the main diagram for the next development phases (design and implementation). The Java programming language is used for developing a system’s prototype, to allow the system’s validation by the customers.